Pemanfaatan Sampah Organik dan Serbuk Kayu Menjadi Biobriket sebagai Energi Alternatif - Retnawati, Eka; Apriani, Isna; Sulastri, Aini (Universitas Andalas, 2023)
The rapid economic and population growth of Pontianak City has triggered an increase in domestic waste. The composition of Pontianak City waste in 2020 is dominated by organic waste (91.8%). The wood processing industry will produce 50% of its waste, as sawdust. One of the efforts to reduce the generation of organic waste and sawdust is to use it as fuel in the form of environmentally friendly bio-briquettes. This paper studies the chemical characteristics of calorific value, moisture content, and ash content as they variations in the composition of the resulting bio-briquettes. The research methods include drying, curing, sieving at 40 mesh, mixing charcoal with 15% starch adhesive, and compaction. The composition variations in this study were sawdust (SG): organic waste (SO) (85%:15%, 75%:25%, and 65%:35%). The results showed that the highest calorific value was found in the composition variation of sawdust (SG) at 85%:15% organic waste (SO) of 49 cal/gr, while the highest water content was 20.52% and the highest ash content was 14.57% in the variation of the composition of sawdust (SG) 65%:35% organic waste (SO). The results of the chemical characteristics of calorific value, moisture content, and ash content of bio-briquettes did not meet the requirements of SNI 01-6235-2000. Keywords: bio-briquettes, alternative energy, organic waste, sawdust ABSTRAK Pesatnya pertumbuhan ekonomi dan penduduk Kota Pontianak memicu peningkatan sampah domestik. Komposisi sampah Kota Pontianak tahun 2020 didominasi oleh sampah organik (91,8%). Industri pengolahan kayu akan menghasilkan 50% limbahnya berupa serbuk gergaji. Salah satu upaya untuk mengurangi timbulan sampah organik dan serbuk gergaji adalah dengan memanfaatkannya sebagai bahan bakar berupa biobriket ramah lingkungan. Makalah ini mempelajari karakteristik kimia nilai kalor, kadar air, dan kadar abu sebagai variasi komposisi biobriket yang dihasilkan. Metode penelitian meliputi pengeringan, pemeraman, pengayakan pada ukuran 40 mesh, pencampuran arang dengan perekat kanji 15%, dan pemadatan. Variasi komposisi pada penelitian ini adalah serbuk gergaji (SG): sampah organik (SO) (85% : 15%, 75% : 25%, dan 65% : 35%). Hasil penelitian menunjukkan bahwa nilai kalor tertinggi terdapat pada variasi komposisi serbuk gergaji (SG) 85% : 15% sampah organik (SO) sebesar 49kal/gr, sedangkan kadar air tertinggi 20,52% dan kadar abu tertinggi 14,57% pada variasi komposisi serbuk gergaji (SG) 65% : 35% sampah organik (SO). Hasil karakteristik kimia nilai kalor, kadar air dan kadar abu biobriket tidak memenuhi persyaratan SNI 01-6235-2000. Kata kunci: biobriket, energi alternatif, sampah organik, serbuk gergaji